The impact of GST on the spending pattern of students from the Faculty of Accountancy, UiTM Puncak Alam, Selangor / Nadiah Abdul Hamid ...[et al.] - Abd Hamid, Nadiah; Harun, Nurul Mardhiah; Ahmad, Bedah; Yahya, Mastora (Universiti Teknologi MARA Cawangan Selangor, 2016)
The implementation of GST in Malaysia as of 1st April 2015, which replaced the current Sales and Service Tax (SST) is viewed as a more efficient tax to manage and to generate greater revenue collection for the government. This multi-tiered tax rate of 6 percent is finally borne by the end users who consumed the goods and services regardless of their income levels. As a result, even non-income earners such as students are inevitably bearing the rising price of their consumed goods and services. This study aimed to investigate the level of GST knowledge among the final year students in the Faculty of Accountancy, UiTM Puncak Alam. The students’ knowledge and perception on issues related to GST implementation were found to have certain impacts on their spending pattern. Evidently, the findings revealed that students who have much information about GST implementation and in cases where they perceived that GST is an unfair and unequitable tax system, both situations are highly likely to have significant effects on their spending trend.